Improving The 8⁹ Grade Student's Speaking Ability Using Pictures at SMP Negeri 1 Pulau-Pulau Aru - Suwarno, Titin Arunia; Maitimu, Chara Eirene Elnita (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2024)
This research aimed to improve students' English-speaking ability using visual media with a descriptive quantitative approach. This approach enabled the researcher to measure students' fluency in speaking English. The research posed two questions: How can students' speaking ability be enhanced through teaching with pictures? And how do students feel about speaking instruction using pictures? The study focused on improving the speaking ability of 8⁹-grade students at SMP Negeri 1 Pulau-Pulau Aru. The research employed classroom action research (PTK) as the methodology, consisting of two cycles. The participants included 31 students, the teacher who conducted the teaching in the research, and the researcher as an observer. Data collection involved tests and questionnaires, yielding quantitative data with a descriptive approach. The researcher used a descriptive approach to measure students' fluency based on specific criteria, with values categorized as follows: 130 = very good, 91-130 = good, 51-90 = fair, and 0-50 = poor. In the first cycle, during the pre-test, only 7 out of 31 students scored